Comparative Effectiveness of Brain Hemisphere Training and Neurofeedback Therapy on Creativity in Students with Academic Underachievement - Tavakoli, Farahnaz; Pirani, Zabih; Zanganeh, Firouzeh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The aim of the present study was to compare the effectiveness of brain hemisphere training and neurofeedback therapy on creativity among second-grade elementary students with academic underachievement in Isfahan.Methods and Materials: This study was applied in terms of purpose and employed a quasi-experimental design with a pretest–posttest and follow-up with a control group. The statistical population consisted of second-grade elementary students in Isfahan. In the first stage, purposive sampling was used. Initially, six elementary schools were randomly selected from among the schools in Isfahan, and then all students with academic underachievement in these schools were identified as the sample. Subsequently, 45 students who scored above the cutoff point (0.25) on the creativity test were selected and randomly assigned to three groups of 15 participants each. For the first and second experimental groups, neurofeedback therapy and brain hemisphere training were administered, respectively, while the control group received no intervention. After the training sessions, all three groups were reassessed using the creativity test. The collected data were analyzed using analysis of variance method via SPSS-26 software.Findings: The statistical results indicated that there was a significant difference between the mean scores of the image completion subscale in the brain hemisphere training group and the neurofeedback group. Additionally, there was a significant difference between the brain hemisphere training group and the control group, whereas no significant difference was found between the neurofeedback group and the control group.Conclusion: Based on the findings, it can be concluded that brain hemisphere training improves students’ creativity.